“I cluppe and I cusse as I wood wore”: Erotic Imagery in Middle English Mystical Writings - Witalisz, Władysław (Text Matters: A Journal of Literature, Theory and Culture, 2013)
The mutual influences of the medieval discourse of courtly love and the literary visions of divine love have long been recognized by readers of medieval lyrical poetry and devotional writings. They are especially visible in the affinities between the language used to construct the picture of the ideal courtly lady and the images of the Virgin Mary. Praises of Mary’s physical beauty, strewn with erotic implications, are an example of a strictly male eroticization of the medieval Marian discourse, rooted in Bernard of Clairvaux’s allegorical reading of the Song of Songs, where Mary is imagined as the Bride of the poem, whose “breasts are like two young roes that are twins” (Cant. of Cant. 4:5). Glimpses of medieval female erotic imagination, also employed to express religious meanings, can be found in the writings of the mystical tradition: in England in the books of visions of Margery Kempe, in the anonymous seers of the fourteenth century, and, to some extent, in Julian of Norwich. Though subdued by patriarchal politics and edited by male amanuenses, the female voice can still be heard in the extant texts as it speaks of mystical experience by reference to bodily, somatic and, sometimes, erotic sensations in a manner different from the sensual implications found in the poetry of Marian adoration. The bliss of mystic elation, the ultimate union with God, is, in at least one mystical text, confidently metaphorized as an ecstatic, physical union with the human figure of Christ hanging on the cross.